Cassava root husks as a sorbent material for the uptake and pre-concentration of cadmium(II) from aqueous media - Jorgetto, Alexandre de Oliveira [UNESP]; Silva, Adrielli Cristina Peres da [UNESP]; Cavecci, Bruna [UNESP]; Barbosa, Rodrigo Correa [UNESP]; Martines, Marco Antonio Utrera; Castro, Gustavo Rocha de [UNESP] (My University, 2013)
Cassava husks were undergone to simple processes to obtain a fine powder whose particle diameter varied from 63 μm to 75 μm. The characterization of the material indicated the presence of the groups alcohol, amine and thiocarbonyl. The material was tested through batch experiments and the effect of the contact time and pH over the adsorption of Cd(II) ions were evaluated. The material presented a rapid kinetic equilibrium, which was reached in less than 1 min, and the highest Cd(II) uptake occurred at pH 5. The optimum conditions obtained were applied to determine the material’s maximum adsorption capacity with the aid of the linearized Langmuir equation (0.109 mmol g-1). A pre-concentration experiment was also carried out, and provided a pre-concentration factor of 43-fold.
Keywords: Cassava; Cadmium; Adsorption; Pre-concentration; Solid-phase extraction